PREPARATION AND PROPERTIES OF PA6/PP/ORGANOCLAY NANOCOMPOSITES OBTAINED BY MELT COMPOUNDING - , Kusmono, Z.A. Mohd Ishak, W.S. Chow, T. Takeichi, Rochmadi ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Nanocomposites based on polyamide 6/polypropylene (PA6/PP = 70/30 parts), containing 0, 2, 4, 6, 8, 10 phr of organoclay, and maleic anhydride grafted polypropylene (PP-g-MA) as a compatibilizer were prepared by melt compounding using counter-rotating twin-screw extruder followed by injection molding. X-ray diffraction (XRD) and transmission electron microscope (TEM) were used to characterize the structure of nanocomposites. The mechanical properties of the nanocomposites were determined by tensile test. XRD and TEM results indicated the formation of the exfoliated nanocomposites at low organoclay content (up to 4 phr), and a mixture of intercalated and exfoliated nanocomposites at high organoclay content (10 phr). The PP-g-MA addition yielded finer dispersion of nanoclay than without compatibilizer. Tensile modulus increased with increasing organoclay content